Organisation and financing of preterm baby care system - Obłoza, Beata; Raba, Grzegorz; Fudali-Walczak, Magdalena (European Journal of Clinical and Experimental Medicine, 2015)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The preterm birth is the one of the biggest problem of the modern perinatology, because 85% of newborn mortality is caused by prematurity. Three-level of the perinatology system is introduced in Poland. The main objective of this system is to pursuit to reduce mortality rate of newbornbabies with low birth weight. Logistics system activity in that manner needs appropriate funding. In order to proper valuation of the procedures, there is a need to depict preterm infants care specific organization. The financing level of the preterm infants care in Poland is too low. This is a worrying phenomenon due to the fact that the care and treatment costs of preterm infants are constantly growing. This applies not only to medications but also wound care products, equipments and specialized care. On the other hand, the financial expenditures have not increased, which can cause a decrease in the level of care.